1996
DOI: 10.1172/jci118482
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection may affect gene therapy success. Dominant negative effects observed for ornithine transcarbamylase in mouse and human hepatocytes.

Abstract: We have achieved significant improvement of ornithine transcarbamylase deficiency (OTCD) in a mouse model through adenoviral-mediated gene transfer of the human ornithine transcarbamylase cDNA. Substantial reduction in orotic aciduria was observed within 24 h of treatment. Metabolic correction was later associated with phenotypic correction and moderate increase in enzymatic activity. In an effort to identify the level of gene expression required to achieve wild-type levels of enzyme activity we uncovered a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…18 Systemic delivery of Ad5-based vectors in mice invariably leads to preferential transduction of hepatocytes, which are known to express CAR to high levels. 10,14,55,56 The pathway involved in this uptake is however complex and remains largely unknown. On the one hand, several reports suggest that fiber-CAR interactions are primarily responsible for the natural tropism of Ad5-based vectors for the liver.…”
Section: Discussionmentioning
confidence: 99%
“…18 Systemic delivery of Ad5-based vectors in mice invariably leads to preferential transduction of hepatocytes, which are known to express CAR to high levels. 10,14,55,56 The pathway involved in this uptake is however complex and remains largely unknown. On the one hand, several reports suggest that fiber-CAR interactions are primarily responsible for the natural tropism of Ad5-based vectors for the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this phenomenon has been reported in vitro. 3 The OTC protein is predominantly expressed in the liver and intestinal mucosa as an inactive precursor polypeptide containing an N-terminal leader sequence. On transport to the mitochondria the leader sequence is cleaved and the protein assembled into an active homotrimeric form that catalyses conversion of ornithine and carbamyl phosphate to citrulline and inorganic phosphate.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…7 Studies by other researchers have shown that co-expression of both wild-type and mutant OTC substantially inhibited wild-type enzyme activity, suggesting the R92Q mutation exerts a dominant-negative effect, at least in vitro. 3 The next two mutations result in amino acid substitutions R141Q or K88N and produce a severe neonatal 8 or late presenting phenotype, 9 respectively. Mutation R141Q affects the carbamyl phosphate-binding site without altering the tertiary structure of the protein 10 whereas K88N alters a lysine residue in the substrate-binding site of OTC.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a wild-type OTC gene is expressed within the same cell, it is unknown whether the mutant polypeptide that is being simultaneously synthesized by the cell will interfere with the assembly of a wild-type trimer and thus exert a dominant negative effect. One previous study suggested that such a phenomenon may occur in the OTC protein (10).…”
mentioning
confidence: 93%